Use of third person atonic pronouns in the oral Spanish of Pucallpa - Britto La Torre, Jacqueline Delicia (2016)
Nouns, noun phrases and subordinate clauses that function syntactically as direct and indirect objects may be represented in Spanish by the unstressed third person pronouns le, lo and la. These pronouns are used differently in the oral Spanish of Pucallpa depending on whether the speaker is of Shipibo origins, is Andean, or is a native Spanish speaker. The speaker’s educational level also typically plays a part in pronoun use. The speakers with higher education use the pronominal forms for syntactic functions in ways closest to the norm, while those with only primary or secondary school use the forms in ways farthest from the norm. The omission of pronouns was found to be a recurring phenomenon in the Spanish of speakers of all educational levels. Those who also speak Shipibo omitted the most pronouns, followed by those of Andean origin, followed by those whose mother tongue is the Spanish of Pucallpa.